Technology of storage of siloss from LMK - Chebanov, L.; Chertkov, O.; Savchenko, V.; Romankov, D.; Kupko, K.; Mykolyuk, V.; Scherbak, A. (Ways to Improve Construction Efficiency, 2019)
Metal silos are a modern and popular way of storing grain; Despite the apparent simplicity; they are complex engineering structures that require accurate calculation taking into account all the features of design and construction; operation and location of their location. The choice of silo type is both a problem and a problem: Structurally; modern silos are executed in several variants; depending on the way of storage of products and their removal. The assembly of silos from prefabricated galvanized structures by lifting and raising tiers allows you to perform basic work directly at the level of the construction site.